Optimization of Pulsed Laser Deposition Parameters for Single-Crystalline (011) Oriented Tetragonal Pzt Thin Films - Mtebwa, Mahamudu (Tanzania Journal of Engineering and Technology, 2023)
Recent advances in nanotechnology applications require the processing of high-quality thin films. A systematic study of the optimization of Pulsed deposition parameters for (110) oriented tetragonal PZT thin films is reported in this work. Prior to film deposition, a highly tetragonal Pb(Zr0.5, Ti0.95) or PZT 05/95 was selected to be deposited on (110) oriented Strontium titanate, SrTiO3 substrate, STO(110) to insure small compressive misfit strain. Unlike SRO, the LSOM bottom electrode was then successfully grown at 620 °C, 1.0 J/cm2 and a target-substrate distance of 3.9 cm. Finally, deposition parameters of PZT were progressively optimized through monitoring film morphological changes. Monocrystalline PZT films of different thicknesses with layer €“by €“layer growth mode were finally realized at a deposition temperature of 550 °C, laser energy of 1.0 J/cm2, background pressure of 200 mTorr O2, while deposition rate was 3 Hz and target-substrate distance of 3.1 cm. The optimal film growth rate was finally estimated to be 0.3 nm/100 Pulses. Keyword: PZT, SRO, LSOM, Thin Pulsed Laser Deposition, Epitaxy, Film